2017
DOI: 10.1007/s10964-017-0728-y
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood, Family, and Peer Factors Associated with Early Adolescent Smoking and Alcohol Use

Abstract: There is broad agreement that neighborhood contexts are important for adolescent development, but there is less consensus about their association with adolescent smoking and alcohol use. Few studies have examined associations between neighborhood socioeconomic contexts and smoking and alcohol use while also accounting for differences in family and peer risk factors for substance use. Data drawn from the Seattle Social Development Project (N = 808), a gender-balanced (female = 49%), multiethnic, theory-driven l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 74 publications
(130 reference statements)
7
67
2
6
Order By: Relevance
“…Thus, it is likely that the social learning effects of adults’ alcohol and cigarette use on adolescent behavior were present prior to middle school and are relatively constant. Also, for the nominated “most important adults” who were adolescents’ parents, concordance may also reflect shared genetic or environmental risk factors (Cambron, Kosterman, Catalano, Guttmannova, & Hawkins, 2018), which may be relatively stable across time. In contrast, concordance with adult marijuana use did vary by grade, peaking in middle school and then remaining more constant throughout high school.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that the social learning effects of adults’ alcohol and cigarette use on adolescent behavior were present prior to middle school and are relatively constant. Also, for the nominated “most important adults” who were adolescents’ parents, concordance may also reflect shared genetic or environmental risk factors (Cambron, Kosterman, Catalano, Guttmannova, & Hawkins, 2018), which may be relatively stable across time. In contrast, concordance with adult marijuana use did vary by grade, peaking in middle school and then remaining more constant throughout high school.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the school environment is a contributing factor to peer influences on smoking. An individual's peer network and reflective school norms have been shown to be significantly associated with smoking (21,22). Another item was the percentage of students who reported having attended HIV/AIDS class in school, due to its inclusion in Tennessee's comprehensive health education program (23).…”
Section: School Level Variablesmentioning
confidence: 99%
“…Several studies have suggested peer influence as being the most important and consistent factors of adolescent tobacco use (10,20,24,25). The risk of an adolescent currently smoking is significantly associated with their peer network especially if one or two best friends smoke (21). The logic of classifying this variable on the class level relates to proximity of peers within same classes and recognized associations between peers and smoking status.…”
Section: Class Level Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies on factors related to youth smoking [4,11] and various programs, such as student counselling and health education to encourage smoking cessation and prevent secondhand smoke exposure, [12][13][14][15] have been developed. However, there is a lack of sequential intervention programs that aim to understand the factors related to teen tobacco use, provide in-depth and continuous management of teen smoking, and initiate a change in attitudes toward smoking by incorporating a meaningful vision into their lives.…”
Section: Introductionmentioning
confidence: 99%